The Effect of Effleurage Massage on Reducing Labor Pain in Laboring Mothers at Puskesmas Sarimotandang Sidamanik Year 2022 - Fithri, Nurhamida (Pena Cendekia Insani, 2024)
Context: Epidural massage, also known as massage, is a type of skin stimulation employed to effectively alleviate pain during childbirth. The purpose of this research is to determine whether or not massage effleurage can alleviate labor pain in the mother. This is an analytical study employing an experimental design with a pre- and post-test for a single group. The study sample comprised 35 individuals who were in labor and were mothers at the Sarimotandang Health Center. Through the distribution of questionnaires to respondents, data was gathered. Data cleansing, tabulating, editing, coding, and entry are the initial steps in data processing. Analyzing data with the paired T test. Findings: An effect of effleurage massage on labor pain in laboring mothers was observed both prior to and following the intervention (p = 0.000). In conclusion, it is advisable for the expectant mother to seek guidance from healthcare professionals regarding the issue of labor pain.